A Description of Risk Factors for Non-alcoholic Fatty Liver Disease in the Southern Community Cohort Study: A Nested Case-Control Study - Sarkar, Sudipa; Lipworth, Loren; Kabagambe, Edmond K.; Bian, Aihua; Stewart, Thomas G.; Blot, William J.; Ikizler, T. Alp; Hung, Adriana M. (Frontiers in Nutrition, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with obesity and hypercholesterolemia. In addition, total fat and folate intake have been associated with NAFLD. Aims: We investigated risk factors for NAFLD among individuals of largely low socioeconomic status, and whether these associations differed by race. Methods: A nested case-control study was conducted within the Southern Community Cohort Study. Through linkage of the cohort with Centers for Medicare and Medicaid Services, International Classification of Diseases, Ninth Revision, Clinical Modification codes were used to identify incident NAFLD cases. Controls were matched 4:1 to cases on enrollment age, sex, and race. A logistic regression was used to estimate odds ratios for the associations of NAFLD with covariates of interest. Results: Neither total fat nor folate intake was significantly associated with NAFLD. Hypercholesterolemia (odds ratio 1.21) and body mass index (75th versus 25th percentile) for blacks (odds ratio 1.96) and whites (odds ratio 2.33) were associated with an increased risk of non-alcoholic fatty liver disease. No significant interaction with race for any of the studied variables was noted. Conclusions: Both hypercholesterolemia and increasing body mass index, but not total fat and folate intake, were risk factors for NAFLD in the Southern Community Cohort Study.